코로나-19 기간 이주 근로자의 주관적 건강 상태 영향 요인 - 강수진; 김민채; Kang, Soo Jin; Kim, Min Chae (한국직업건강간호학회지, 2025)
Purpose: This study aimed to measure migrant workers' self-rated health and identify its influencing factors. Methods: Between August and September 2021, 400 migrant workers in Korea completed a web-based survey. Self-rated health was measured using one question and categorized as 'good'or 'poor.'Multivariate logistic regression was performed to investigate associated factors, including demographic and work-related variables, social support, subjective health literacy, and depression. Results: Overall, 36.7% of participants had poor self-rated health. The odds ratios for poor self-rated health were high among participants who reported 5~7 days/week night shift work (adjusted=OR 5.34, 95% CI: 2.30~12.35) or 1~4 days/week night shift work (adjusted OR=4.13, 95% CI: 2.01~8.00) compared to those who do not work night shifts. Other significant factors included depression (adjusted OR=1.05, 95% CI: 1.02~1.10) and social support (adjusted OR=0.38, 95% CI: 0.25~0.58). Health literacy was not significantly associated with self-rated health. Conclusion: During the COVID-19 pandemic, migrant workers reported poorer subjective health status. Therefore, strategies aimed at improving working conditions and bolstering mental health through social support are required to enhance their health.